INCIDENCE OF RUBELLA IN NORTH WEST RUSSIA ON THE STAGE OF ELIMINATION OF RUBELLA - M. A. Bichurina (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Analysis of incidence of Rubella in the period of 2001–2013 on the territory of North West Federal Region of Russia evidences that the large scaled vaccination in the frames of the “Public Health” National Project considerably influenced the epidemical process of the rubella virus infection (RVI). However at the same time besides the drastic decrease of Rubella incidence to sporadic level (0.4 per 100 000 in 2013) and limited transmission of RVI the shift of Rubella incidence to the eldest age groups was observed: 94% of patients with RVI in 2013 were more than 17 years old. Among Rubella cases the vaccinated patients consisted 3.7% in 2013 and revaccinated 7.1% in 2012. According to gender distribution males with RVI were revealed more frequently than females. The outbreak of Rubella in one of the Military Colleges is described. At present time RV strains of 2B genotype circulate in North West Russia. Cases of wrong clinical diagnosis of Rubella were revealed: in 2011–2013 only for 19% of patients the Rubella was laboratory confirmed. Thus on the stage of the elimination of Rubella the verification of each Rubella case is extremely necessary.